2013
DOI: 10.1039/c3cp50805f
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of the novel theory explaining self-organization in porous anodic alumina films

Abstract: The lack of a reliable method for theoretical prediction of nanoporous anodic alumina films obtained from non-familiar electrolytes prompted the search of a viable solution to this problem. The theory explaining the self-assembly mechanism was described in our preceding work. Here, the results of an extensive validation test are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 15 publications
1
49
0
Order By: Relevance
“…On the other hand, poorly arranged nanoporous structures are formed by chromic acid anodizing due to pore branching. Several carboxylic acids, including oxalic ((COOH) 2 ) [35][36][37][38], malonic (HOOC-CH 2 -COOH) [39][40][41], tartalic (HOOC-(CHOH) 2 -COOH) [42][43][44], citric (HOOC-CH 2 -C(OH)(COOH)-CH 2 -COOH) [45][46][47], malic (HOOC-CH(OH)-CH 2 -COOH) [45,48], glycolic (HOOC-CH 2 OH) [45], formic (HCOOH) [49], and tartronic (HOOC-CH(OH)-COOH) [50] acid have been reported to date for the fabrication of anodic porous alumina. Oxalic and malonic acid anodizing have been reported to give rise to self-ordering behavior under suitable anodizing conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, poorly arranged nanoporous structures are formed by chromic acid anodizing due to pore branching. Several carboxylic acids, including oxalic ((COOH) 2 ) [35][36][37][38], malonic (HOOC-CH 2 -COOH) [39][40][41], tartalic (HOOC-(CHOH) 2 -COOH) [42][43][44], citric (HOOC-CH 2 -C(OH)(COOH)-CH 2 -COOH) [45][46][47], malic (HOOC-CH(OH)-CH 2 -COOH) [45,48], glycolic (HOOC-CH 2 OH) [45], formic (HCOOH) [49], and tartronic (HOOC-CH(OH)-COOH) [50] acid have been reported to date for the fabrication of anodic porous alumina. Oxalic and malonic acid anodizing have been reported to give rise to self-ordering behavior under suitable anodizing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The sealing process causes the formation of a highly crystalline hydroxide layer on the surface of the anodic oxide, and the hydroxide layer is highly dissolution-resistant in acidic and alkaline solutions. Using these characteristic structural and chemical properties, anodic porous alumina has been widely investigated for many applications: antireflection structures [7,8] [50] acid have been reported to date for the fabrication of anodic porous alumina. Oxalic and malonic acid anodizing have been reported to give rise to self-ordering behavior under suitable anodizing conditions.…”
mentioning
confidence: 99%
“…However, malonic and tartaric acids have seldom been used for nanostructure fabrication because they do not perform as well with regards to self-ordering as the three major electrolytes. Chromic (H 2 CrO 4 ) [41][42][43], formic (HCOOH) [44], malic (HOOC-CH(OH)-CH 2 -COOH) [27,45,46], citric (HOOC-CH 2 -C(OH)(COOH)-CH 2 -COOH) [27,47,48], glycolic (CH 2 OH-COOH) [27], squaric (3,4-dihydroxy-3-cyclobutene-1,2-dione) [49], tartronic (HOOC-CH(OH)-COOH) [50], and acetylenedicarboxylic (HOOC-C≡C-COOH) [51] acids have also been reported as electrolytes used to fabricate porous alumina that has characteristic nanostructure morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Anodic porous alumina is typically fabricated on an aluminum substrate using electrochemical anodizing (or anodization) [22][23][24][25][26]. In several acidic electrolyte solutions, the porous alumina fabricated by anodizing is self-ordered when prepared at the appropriate electrochemical conditions, including appropriate concentrations, temperatures, and voltages (or electrochemical potentials) [27][28][29][30] [50], and acetylenedicarboxylic (HOOC-C≡C-COOH) [51] acids have also been reported as electrolytes used to fabricate porous alumina that has characteristic nanostructure morphologies.In addition to these acidic electrolytes, alkaline and neutral solutions used for porous alumina fabrication were reported by several research groups. Takahashi et al reported that a porous anodic oxide film could be formed by anodizing in an H 3 BO 3 /Na 2 B 4 O 7 neutral borate solution at a high temperature [52].…”
mentioning
confidence: 99%
“…Cyclic oxocarbonic acids such as squaric [24], croconic, and rhodizonic [25] acid were very recently determined to be suitable organic electrolytes for fabricating porous alumina, although the details of the growth behavior are still unknown. Carboxylic acids can also be employed as suitable electrolytes for fabricating porous alumina, including oxalic [26,27], malonic [28,29], citric [30,31], malic [32], acetylenedicarboxylic [33], tartaric [34,35], tartronic [36], glycolic [37], and formic [38] acid. Because the nanostructural features and chemical properties of anodic porous alumina are determined and limited by the electrolyte used [39], the discovery of a new suitable electrolyte would expand the applicability of porous alumina.…”
Section: Introductionmentioning
confidence: 99%